Feeling terrified? the emotions of online violent extremism - Waldek, Lise ca. 20./21. Jh; Droogan, Julian ca. 20./21. Jh; Lumby, Catharine 1961- (Cambridge elements, 2021)
This Element presents original research into how young people interact with violent extremist material, including terrorist propaganda, when online. It explores a series of emotional and behavioural responses that challenge assumptions that terror or trauma are the primary emotional responses to these online environments. It situates young people's emotional responses within a social framework, revealing them to have a relatively sophisticated relationship with violent extremism on social media that challenges simplistic concerns about processes of radicalisation. The Element draws on four years of research, including quantitative surveys and qualitative focus groups with young people, and presents a unique perspective drawn from young people's experiences